2019 IEEE International Conference on Software Maintenance and Evolution (ICSME) 2019
DOI: 10.1109/icsme.2019.00013
|View full text |Cite
|
Sign up to set email alerts
|

Do Energy-Oriented Changes Hinder Maintainability?

Abstract: Energy efficiency is a crucial quality requirement for mobile applications. However, improving energy efficiency is far from trivial as developers lack the knowledge and tools to aid in this activity. In this paper we study the impact of changes to improve energy efficiency on the maintainability of Android applications. Using a dataset containing 539 energy efficiencyoriented commits, we measure maintainability -as computed by the Software Improvement Group's web-based source code analysis service Better Code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Other tools perform security assessment, automated test case generation and detection of non-functional issues such as energy consumption [270], [271]. While fixing non-functional performance bugs, developers need to consider the threat of introducing functional bugs [272] and hindering code maintainability [273]. In this context, Linares et al [274] suggested that developers rarely implement micro-optimizations (e.g., changes at statement level).…”
Section: Developer Perspectivementioning
confidence: 99%
“…Other tools perform security assessment, automated test case generation and detection of non-functional issues such as energy consumption [270], [271]. While fixing non-functional performance bugs, developers need to consider the threat of introducing functional bugs [272] and hindering code maintainability [273]. In this context, Linares et al [274] suggested that developers rarely implement micro-optimizations (e.g., changes at statement level).…”
Section: Developer Perspectivementioning
confidence: 99%
“…Linking maintainability to the energy efficiency of Android software is the work of Cruz et al (2019). In this article, the authors study the impact of changes designed to improve energy efficiency on the maintainability of Android applications.…”
Section: Related Workmentioning
confidence: 99%
“…Namely [14] are the ones more directly related with our current work, as they attempt to evaluate the relationship between maintainability measures and energy consumption. However, Hindle (2015) focused on only one measure (lines of code) for the evaluation and the study by Cruz et al (2019) is focused on a different domain (Android applications).…”
Section: Related Workmentioning
confidence: 99%
“…Further, there are domain-specific research that share similar goals. For instance, some studies focus on mining energyaware commits in the Android ecosystem [7]; mining energyaware commits and pull-requests in Android and iOS ecosystems and then building a catalog of mobile energy patterns [16]; or investigating if energy-aware commits have any impact on maintainability metrics [17]. These studies share a common limitation: since they rely on mining techniques, they do not measure the actual energy consumption data, and some of the solutions to energy-related problems might be limited to the understanding of the specific developers.…”
Section: Related Workmentioning
confidence: 99%